1981
DOI: 10.1159/000137515
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Genetically Controlled Deficiency in Debrisoquine Hydroxylation on Antipyrine Metabolite Formation

Abstract: The influence of the genetically controlled deficiency in debrisoquine hydroxylation on antipyrine metabolite formation was studied by giving 500 mg antipyrine to 14 extensive and 10 poor metabolizers of debrisoquine. The pharmacokinetics of antipyrine were determined on the basis of the saliva concentration time curve and the cumulative urinary excretion of 4-hydroxyantipyrine, norañtipyrine, 3-hydroxymethyl-antipyrine, and 3-carboxyantipyrine was measured for 32 h following drug administration. Antipyrine el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
1

Year Published

1982
1982
1996
1996

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 8 publications
1
4
1
Order By: Relevance
“…Others have reported no difference in antipyrine clearance and half-life between extensive and poor metabolizers of debrisoquin, although there was a trend for lower urinary excretion of 3-OHM. 34 We noted no such trend in our PM subject.…”
Section: Discussioncontrasting
confidence: 48%
“…Others have reported no difference in antipyrine clearance and half-life between extensive and poor metabolizers of debrisoquin, although there was a trend for lower urinary excretion of 3-OHM. 34 We noted no such trend in our PM subject.…”
Section: Discussioncontrasting
confidence: 48%
“…These statistically significant intraindividual correlations, together with closely similar frequencies for the genes that control each AP rate constant (Table II), suggested that a single genetic locus might control variations in all three AP rate constants. Though highly statistically significant (<0.001) because of the large number of subjects investigated The polymorphism in drug oxidation revealed using AP as substrate differs from the polymorphism of debrisoquine oxidation (26) since the debrisoquine phenotype of a subject appears unrelated to that subject's capacity to biotransform AP (27,28). Furthermore, the gene frequency of the debrisoquine polymorphism (P = 0.72 and q = 0.28 in a Caucasian population from the United Kingdom [29]) differs from the gene frequencies we observed in the AP polymorphism (Table II).…”
Section: Resultsmentioning
confidence: 99%
“…However, the metabolism of antipyrine, which is quite frequently used as a 'model drug' in clinical pharmacological studies, is not related to sparteine or debrisoquine metabolism. Thus, antipyrine metabolism seems to be carried out by different enzyme systems (Bertilsson et al, 1980;Danhof et al, 1981;, submitted for publication).…”
mentioning
confidence: 99%